To evaluate the efficacy and safety of intravenous bolus versus intravenous infusion of iron sucrose in pregnant women with severe iron deficiency anemia - Verma, Urvashi; Singh, Saroj; Singh, Shikha; Pathak, Anu; Yadav, Poonam; Benazeer, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of present study was to evaluate the efficacy and safety of intravenous bolus iron sucrose for iron deficiency anemia during pregnancy during second and third trimester women presenting at S.N. medical college, Agra. Methods: It was a prospective controlled trial and study was carried out in Department of Obstetrics and Gynecology, S.N. medical college, Agra in the year 2014-2016. 100Pregnant women with proved iron deficiency anemia having hemoglobin between 4-9gm/dl was included in this study. Total Iron deficit was calculated by standard formula. Target haemoglobin was 11gm/dl. Iron sucrose was administered by intravenous bolus and intravenous infusion techniques. Hemoglobin was repeated at 2 weeks, 4 weeks and 8 weeks after the last dose of intravenous iron sucrose Results: In Group A (bolus group n=50) 22 women had gestational age >24-28weeks and 20 women gestational age >18-24 weeks, with Mean gestational age of 24.36±3.78 weeks. In Group B (infusion group n=50) most of the patients 24 (48%) had gestational age >24-28 weeks, 18 (36%) had gestational age >18-24 weeks, with Mean gestational age of 24.94±3.51 weeks. Target hemoglobin was achieved in group A in all 50 (100%) cases and in group B in 49 (98%) cases. There were no allergic reactions. Conclusions: This study showed a significant improvement in the hemoglobin of the patients after receiving intravenous bolus and intravenous infusion of iron sucrose. Patients achieved the target hemoglobin of 11gm/dl. Both therapies are safe, effective and faster acting for the treatment of iron deficiency anaemia during pregnancy. The bolus push technique is more convenient to women and care provider, less time consuming as well as cost effective.